2017
DOI: 10.1080/14786419.2017.1378200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of ethanolic extract of spine, skin and rind of Jack fruit peel – A comparative study

Abstract: The present study was conducted to identify the chemical constituents and evaluate the anti-inflammatory activity of crude ethanolic extracts of spine, skin and rind of jack fruit (Artocarpus heterophyllus) peel. Polyphenol and flavonoid contents were assessed using Folin's Ciocalteu reagent and aluminium chloride methods which revealed 316, 355 and 382 mg tannic acid equivalent/g of polyphenol and 96.7, 131.6 and 164.6 mg quercetin equivalent/g of flavonoid in spine, skin and rind, respectively. Anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Various epidemiological studies conducted on human have confirmed that antioxidants extracted from jackfruit can prevent gastric cancer, lung cancer, prostate cancer, coronary heart disease, myocardial infarction, hypertension etc. [3][4][5]. Both the seeds and pulp of jackfruit are edible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various epidemiological studies conducted on human have confirmed that antioxidants extracted from jackfruit can prevent gastric cancer, lung cancer, prostate cancer, coronary heart disease, myocardial infarction, hypertension etc. [3][4][5]. Both the seeds and pulp of jackfruit are edible.…”
Section: Introductionmentioning
confidence: 99%
“…The ethanolic extraction for jackfruit seed and pulp describing a full 23 factorial experimental design along with corresponding responses.To conduct the experimental design and the statistical analysis, well-known software package R (version 2.14.1) was used in this study. All the tests of statistical significance were based on.…”
mentioning
confidence: 99%
“…TIR domain proteins and RLP33 are well known for foreign pattern recognition and providing immunity to plants from microbes (Burch-Smith and Dinesh-Kumar, 2007; Jamieson et al, 2018). In addition, the two most essential genes of the Flavanoid Biosynthesis Pathway, Chalcone Synthase (CHS) and Flavanone 3-Hydroxylase (F3H) have lineage-specific gene copies and may explain the high flavonoid content of A. heterophyllus (Meera et al, 2018). ASMT (N-Acetylserotonin Methyltransferase) and COMT (Caffeic Acid O-methyltransferase) genes act in the penultimate step of the melatonin pathway (Back et al, 2016; Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Artocarpanone and artocarpin strongly inhibited myeloperoxidase activity of human phagocytes with an IC 50 value of 23.3 μm and have potential to be developed into potent anti-in lammatory agents [23]. Meera, et al [24] studied the anti-in lammatory effect of ethanolic extracts of spine, skin and rind of jack fruit. The results revealed that skin extract exhibited maximum anti-in lammatory activity, rind had preferential inhibition on Cyclooxygenase-2 and spine and skin inhibited both Cyclooxygenase-1 and 2 in vitro.…”
Section: Anti-infl Ammatorymentioning
confidence: 99%